Resolvin D1 Protects Against Ischemia/Reperfusion-Induced Acute Kidney Injury by Increasing Treg Percentages via the ALX/FPR2 Pathway - Luan, Hong; Wang, Chuanxiao; Sun, Jianping; Zhao, Long; Li, Lin; Zhou, Bin; Shao, Shihong; Shen, Xuefei; Xu, Yan (Frontiers in Physiology, 2020)
Aims: To evaluate whether Resolvin D1 attenuates ischemia/reperfusion-induced (IRI) acute kidney injury (AKI) via affecting Tregs. Materials and methods: (1) The IRI-AKI mouse model was established, and RvD1 was injected into the mouse tail vein. Further, the renal function, histological changes, injury markers and serum cytokines were detected at 24 h and 72 h after IRI. Flow cytometry was used to categorize regulatory T cells (Tregs) in the spleen and kidney. (2) Treg cells were stripped with the anti-CD25 antibody blocker PC61 to assess its role in the protective effect of RvD1 on IRI mice. (3) CD4+ T cells were obtained from spleen monocytes by magnetic bead sorting and differentiated into induced Treg (iTreg) cells. The effect of RvD1 on iTreg cell differentiation was observed in vitro. In addition, neutralizing antibodies against the orphan receptor G-protein-coupled receptor 32 (anti-GPR32) and LXA4 receptor (anti-ALX/FPR2), both RvD1 receptor blockers, were used to evaluate the effect of RvD1 on iTreg cell differentiation. (4) Boc-1, an ALX/FPR2 receptor inhibitor, was administered via the tail vein to observe its effects on the ameliorative efficacy of RvD1 in IRI-AKI mice in vivo. Results: In vivo, RvD1 increased Treg percentages, alleviated renal tubular injury and reduced the serum levels of IFN-γ, TNF-α and IL-6 in IRI-AKI mice, while PC61 depleted the number of Tregs and reversed the protective effects of RvD1. In vitro, RvD1 induced the generation of iTregs. Importantly, preincubation with anti-ALX/FPR2 neutralizing antibodies but not with anti-GPR32 neutralizing antibodies, abrogated the enhancement activity of RvD1 on iTregs. In addition, in vivo blockade of the receptor ALX/FPR2 by Boc-1 reversed the beneficial effects of RvD1 on the splenic and kidney Treg percentages, renal tubular injury and serum IFN-γ, TNF-α and IL-6 levels. Conclusion: Our study demonstrates that RvD1 protects against IRI-AKI by increasing the percentages of Tregs via the ALX/FPR2 pathway.